Study of the possibility of producing brine-ripened cheeses from frozen sheep’s milk - V. A. Mordvinova; G. M. Sviridenko; I. L. Ostroukhova; D. V. Ostroukhov (Пищевые системы)
The article presents the results of a study of the quality indicators of brine-ripened cheeses produced from defrosted sheep’s milk. The objects of the study were natural and defrosted sheep’s milk, brine-ripened cheeses from this milk. The study of defrosted sheep’s milk (experiment) was carried out after 10 days of its storage at a temperature of –18 °C followed by defrostation at a temperature of 20 ± 2 °C. The composition of natural sheep’s milk (control) was examined after storage for 24 ± 12 hours at a temperature of 4 ± 2 °C. It has been found that the freezing of milk and its subsequent defrostation did not have a significant effect on the milk solids content, the mass fraction of protein and fat, titrated acidity; however, the mass fraction of calcium decreased, on average, by 20%. Freezing milk did not significantly affect the total number of micro- organisms, including spore aerobic microorganisms and molds. A decrease in the number of somatic cells (from 3.0 to 4.5 times) was found. There were no differences between the control and experimental milk samples in the renneting ability. The level of syneresis of clots in the control sample was 16 ± 1% higher compared to the experimental sample. The cheeses were produced according to the traditional technological scheme of brine-ripened cheese using a production mesophilic bacterial starter culture. The control and experimental cheeses did not differ significantly in physical and chemical parameters. According to the degree of proteolysis, there were no significant differences between the control and experimental variants. In the experimental sample, a decrease in the buffer capacity of the cheese mass was noted in comparison with the control cheeses. The freezing of milk did not have a significant effect on the taste characteristics of the cheeses: in both variants, the cheeses were characterized by a weakly expressed cheese, fermented milk taste with original taste of sheep’s milk. More noticeable differences were found in the consistency of the cheeses. In the control version, the consistency was characterized as tender, slightly brittle; in the experimental version, it was less tender, but brittle and slightly powdery. The greatest deterioration in consistency was observed in the samples of frozen cheese made from natural milk after defrosting; it was characterized as brittle, powdery, crumbly.